Best practices on immunomodulators and biologic agents for ulcerative colitis and Crohn's disease in Asia. Issue 8 (1st July 2019) - Ooi, Choon Jin; Hilmi, Ida; Banerjee, Rupa; Chuah, Sai Wei; Ng, Siew Chien; Wei, Shu Chen; Makharia, Govind K; Pisespongsa, Pises; Chen, Min Hu; Ran, Zhi Hua; Ye, Byong Duk; Park, Dong Il; et al.
Abstract: The Asia–Pacific Working Group on Inflammatory Bowel Disease was established in Cebu, Philippines, under the auspices of the Asia–Pacific Association of Gastroenterology with the goal of improving inflammatory bowel disease care in Asia. This consensus is carried out in collaboration with Asian Organization for Crohn's and Colitis. With biologic agents and biosimilars becoming more established, it is necessary to conduct a review on existing literature and establish a consensus on when and how to introduce biologic agents and biosimilars in conjunction with conventional treatments for ulcerative colitis and Crohn's disease in Asia. These statements also address how pharmacogenetics influences the treatments of ulcerative colitis and Crohn's disease and provides guidance on response monitoring and strategies to restore loss of response. Finally, the review includes statements on how to manage treatment alongside possible hepatitis B and tuberculosis infections, both common in Asia. These statements have been prepared and voted upon by members of inflammatory bowel disease workgroup employing the modified Delphi process. These statements do not intend to be all‐encompassing, and future revisions are likely as new data continue to emerge.